Abnormal coagulation parameters are associated with poor prognosis in patients with novel coronavirus pneumonia - Tang, Ning (J Thromb Haemost, 2020)
BACKGROUND: In the recent outbreak of novel coronavirus infection in Wuhan, China, significantly abnormal coagulation parameters in severe novel coronavirus pneumonia (NCP) cases were a concern. OBJECTIVES: To describe the coagulation feature of patients with NCP. METHODS: Conventional coagulation results and outcomes of 183 consecutive patients with confirmed NCP in Tongji hospital were retrospectively analyzed. RESULTS: The overall mortality was 11.5%, the non‐survivors revealed significantly higher D‐dimer and fibrin degradation product (FDP) levels, longer prothrombin time and activated partial thromboplastin time compared to survivors on admission (P < .05); 71.4% of non‐survivors and 0.6% survivors met the criteria of disseminated intravascular coagulation during their hospital stay. CONCLUSIONS: The present study shows that abnormal coagulation results, especially markedly elevated D‐dimer and FDP are common in deaths with NCP.